(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies occurs in worldwide and more than 70 000 people die of rabies every year. As the disease progresses of patients, more specific neurological symptoms were presented including such as insomnia, anxiety, confusion, slight or partial paralysis, excitation, hallucinations, agitation, difficulty swallowing, and hydrophobia (fear of water). Patients show severe paralysis gradually and eventually dead after a coma. Mice inoculated intramuscularly (i.m.) with CVS-11 (fix strain) showed the severe hind limb paralysis on 7 days and then dead eventually, however mice inoculated with CVS-11 intracerebrally (i.c.) were dead without limb paralysis (Kojima et al. 2009 and Sugiura et al. 2011). For understanding of hind limb paralysis, mice inoculated with CVS- 11, i.m. and i.c. was comparatively analysed by microarray and hisotopathology. Brains and spinal cords of mice were separatively collected after 7 days of the postinoculation of i.m. and i.c.. Viral antigens was similarly observed in both of brains and spinal cords in mice inoculated i.m. and i.c.. Pathologically, microglia was infiltrated in spinal cords in mice inoculated i.m. not but i.c.. In microarray, expression level of genes was normalized with each mock. After comparative analysis of gene expression in mice inoculated i.m. and i.c., significantly (fold change >2, /p/<0.05) changed genes were examined by Ingenuity Pathway Analysis (IPA). As the results, calcium ion related gene and immune response genes including inflammations, chemotaxis, inflammation and apoptosis were obviously up-regulated in i.m. in both of brains and spinal cords. Additionally, the /p/ values of these in spinal cords were obviously lower than those of brains. Moreover, there is significant changes of Stat4, Ifng, Irf7 and Il12 which is the central regulation factors of those responses. The evoked strong immune responses associated with the infiltration of microglia in CNS of mice infected i.m. suggest a reason of damage developed severe paralysis in mice inoculated with CVS-11, i.m.. This work was supported by a grant-inaid for the Health and Labour Science Research Grant from the Ministry of Health, Labour and Welfare of Japan.